(untitled) (Journal of Economic Research & Business Administration, 2015)
Uniform interpretation of the concept «public-private partnership» within modern approaches, as well as the conventional classification of models and forms of public-private partnership, is absent in the literature devoted to questions of public-private partnership, and also in the foreign and Russian legislation. The purpose of public-private partnership consists in association of the best parties of the state and private sectors for mutual benefit, and the variety of forms and models of application of public-private partnership do it by the universal mechanism for the solution of a number of long-term tasks – from creation and infrastructure development before development and adaptation of new perspective technologies. For ensuring participation of the private sector in implementation of socially important infrastructure projects the state has to create balance of risks accepted for both parties and advantages. The paper describes definition of public-private partnership, its distinctive characteristics; classifications of forms and models of public-private partnership